L’aspetto particolare della traduzione di testi antichi. L’arcaizzazione - Salmeri, Claudio (Neophilologica, 2014)
The article deals with an area which has largely escaped the attention of researchers so far, i.e. the strategy of archaisation and modernisation in the translation of older texts. The English and Italian translations of Witold Gombrowicz’s Trans-Atlantyk convoluted style serve as an example of how to employ one of these two completely different strategies. The vocabulary, phrasing and structure of the language Gombrowicz used to write his novel have converged in a literary from known as gawęda, an old form of storytelling. The English version employs a type of faux seventeenth century English. The Italian version, on the other hand, uses a modern language and style. The purpose of this paper is also to analyse two Polish translations of Carlo Goldoni’s La Locandiera. The first translation is archaised, the second one — modernised. The discussion will try to illustrate which strategy seems to be a better solution.